PENGARUH PROFITABILITAS, SOLVABILITAS, OPINI AUDIT, UKURAN PERUSAHAAN, UKURAN KANTOR AKUNTAN PUBLIK, UMUR PERUSAHAAN DAN LABA RUGI PERUSAHAAN TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2012-2016) - Meliana Dian Puspita, 13.05.62.0005; Kartika, Andi (Students Journal of Accounting and Banking, 2017)
This study aims to examine and analyze the effect of profitability, solvency, the auditors opinion, the size of the company, size of public accounting firms, age of the firm and profit and loss company to audit delay on manufacturing companies listed in Indonesia Stock Exchange (BEI). The population of this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) during the years 2012 to 2016 that reported complete financial statements and published in Indonesian Capital Market Directory (ICMD) and IDX website. Samples are included in the criteria of this study were 69 companies using purposive sampling method. Methods of data analysis in this study using multiple linear regression analysis using SPSS 19.Â The results showed that the variables of profitability and the size of the public accounting firms are significant positive effect on audit delay, variable solvency, the auditorâs opinion, the size of the company and age of the firm are not significant negative effect on audit delay, and variable profit and loss company is not significant positif effect on audit delay.Keywords: Audit Delay, Profitability, Solvency, The Auditors Opinion, The Size of The Company, The Size of The Public Accounting Firm (KAP), The Age of The Company and Profit and Loss Company